Penyuluhan ASI Eksklusif sebagai Intervensi Promotif dan Preventif di Komunitas - Jannah, Miftahul; Herawati, Fitria; Soendari; Waslikha, Siti; Masruroh (Universitas Ngudi Waluyo, 2025)
Breastfeeding (Exclusive Breastfeeding) is one of the most effective ways to ensure the health and survival of children. Breastfeeding will improve sensory and cognitive abilities and protect children from infectious and chronic diseases. Poor infant feeding practices can have an impact on children's growth and development. Factors causing non-exclusive breastfeeding in infants include the mother's workload, promotion of formula milk, lack of support for breastfeeding in public places, lack of realistic information on breastfeeding experiences, different perceptions of family members in breastfeeding, maternal knowledge factors, and socio-economic factors. The purpose of community service is to increase the knowledge of breastfeeding mothers about the benefits of exclusive breastfeeding. The Community Service Method will be implemented in 3 stages, namely the First Stage is to prepare by conducting a problem assessment and collaborating with partners. The Second Stage is to conduct a pre-test to explore the level of knowledge of breastfeeding mothers, provide counseling on exclusive breastfeeding using leaflet media. The Third Stage is to conduct an evaluation by providing a post-test to breastfeeding mothers. From the results of Community Service, it was found that this activity was attended by 35 breastfeeding mothers. The results showed that before the counseling, the pretest value of breastfeeding mothers' knowledge showed the lowest value of 30 and the highest was 70, while the average value was 43.71. After the counseling, the mother's knowledge value showed the lowest value of 80 and the highest was 100, while the average value was 93.43. In conclusion, there was an increase in breastfeeding mothers' knowledge about exclusive breastfeeding. It is hoped that health workers will improve health education to the community, especially pregnant, giving birth and breastfeeding mothers about the benefits of exclusive breastfeeding in order to improve infant health and coverage of exclusive breastfeeding. Abstrak Menyusui (Asi Ekslusif) adalah salah satu cara paling efektif untuk memastikan kesehatan dan kelangsungan hidup anak. ASI akan meningkatkan kemampuan sensorik dan kognitif serta melindungi anak dari penyakit menular dan kronis. Praktik pemberian makanan bayi yang buruk dapat berdampak pada pertumbuhan dan perkembangan anak. Faktor penyebab tidak diberikannya ASI eksklusif pada bayi antara lain karena beban kerja ibu, promosi susu formula, kurangnya dukungan penerimaan menyusui di tempat umum, kurang informasi realistis pengalaman menyusui, persepsi anggota keluarga yang berbeda dalam pemberian ASI, faktor pengetahuan ibu, dan faktor sosial ekonomi. Tujuan pengabdian masyarakat adalah untuk meningkatkan pengetahuan ibu menyusui mengenai manfaat asi ekslusif. Metode Pengabdian Masyarakat akan dilaksanakan dalam 3 tahap yaitu Tahap Pertama melakukan persiapan dengan cara melakukan pengkajian permasalahan dan kerja sama dengan mitra. Tahap Kedua melakukan prestest untuk menggali tingkat pengetahuan ibu menyusui, memberikan penyuluhan mengenai asi ekslusif menggunakan media leflet. Tahap Ketiga Melakukan evaluasi dengan cara memberikan posttest kepada ibu menyusui. Dari hasil pengabdian Masyarakat didapatkan bahwa kegiatan ini diikuti oleh 35 orang ibu menyusui. Didapatkan hasil bahwa sebelum penyuluhan, nilai pretest pengetahuan ibu menyusui menunjukan hasil nilai terendah yaitu 30 dan tertingginya yaitu 70, sementara nilai rata-ratanya yaitu 43,71. Setelah dilakukan penyuluhan, nilai pengetahuan ibu menunjukkan hasil nilai terendah yaitu 80 dan tertingginya yaitu 100, sementara nilai rata-ratanya yaitu 93,43. Kesimpulan, terjadi peningkatan pengetahuan ibu menyusui mengenai asi ekslusif. Diharapkan tenaga kesehatan meningkatkan edukasi kesehatan kepada masayarakat, terutama ibu hamil, bersalin dan menyusui mengenai manfaat asi eklusif guna meningkatkan kesehatan bayi dan cakupan asi ekslusif.